Small Differences That Matter: Mistakes in Applying to College - Pallais, Amanda (Journal of Labor Economics, 2015)
In 1997, the ACT increased the number of free score reports it provided to students from three to four, maintaining a $6 marginal cost for each additional report. In response to this $6 cost change, ACT-takers sent many more score reports and applications relative to SAT-takers. They widened the range of colleges they sent scores to, and low-income ACT-takers attended more-selective colleges. Back-of-the-envelope calculations suggest that the policy substantially increased low-income students’ expected earnings. This sizable behavioral change in response to such a small cost change suggests that in this setting, small policy perturbations can have large effects on welfare.